(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay starts from the years of my first acquaintance with Guido, then it focuses on the months that culminate in his death, highlighting his philosophical way of living it, calling to witness his last life partner, Carla Cantini. Hence the essay expands to his characteristic way of being, both in life and philosophy, reminding topics that join him to the years of his education in that way of thought that Fulvio Papi calls “School of Milan”.